دراسة تجريبية للتقطير الشمسي في مدينة اللاذقية - أسمر هيثم (Latakia University Journal -Engineering Sciences Series, 2019)
يستعرض هذا البحث قياسات تجريبية للإشعاع الشمسي في مدينة اللاذقية ونتائج تجارب التقطير الشمسي في أيام مختلفة من حيث الشروط المناخية خلال صيف عام 2002 م، وذلك بهدف تطوير إمكانية استثمار الطاقة الشمسية حيث تم حساب إنتاجية المقطر الشمسي وكذلك دراسة السلوك الحراري للمقطر. وفي نهاية البحث تم مناقشة النتائج وإدراج الحلول والتوصيات لتطوير عملية التقطير الشمسي واستخدام أمثل للطاقة الشمسية في تحلية مياه البحر. This paper presents an experimental measurements of solar radiation in Lattakia City, and the results of the experiments on the solar distillation in various weather conditions during Summer of 2002, in order to develop the possibility of exploiting the solar energy applications. The productivity of the Solar Distiller has been calculated, and the thermal behavior of the Distiller have been studied in six experiments. The Research concludes with a summary of the results and the suggestions of solutions and recommendations for developing the solar distillation process and the optimum use of solar energy .